Occurence of microplastics in the gastrointestinal tract of Selar crumenophthalmus (Bigeye scad) sold in San Jose public market. - Genovata, Rei Marie Joyce Sembrano (2019.)
Microplastic ingestion has been reported for endangered marine species in the Philippines, but microplastic ingestion in commercial fish species is less known. The aim of this study was to assess the occurrence of microplastic ingestion in Selar crumenophthalmus in San Jose, Antique. Thirty guts of S. crumenophthalmus were dissected and analyzed for microplastics ingestion. 73.3% of the gastrointestinal tracts contained microplastics with an average of 4.83 ± 13.42 (SD) particles per total fish. Of the 74 microplastic particles extracted, the most prevalent were: nanoplastics (71.6%), blue (75.7%), and fibers (73%). Cythomoid isopods were also extracted from the branchial cavities of S. crumenophthalmus. This indicates that S. crumenophthalmus is highly vulnerable to microplastic ingestion and can be used as candidate species to monitor microplastic pollution in pelagic waters.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Bigeye scad; Selar crumenophthalmus